The effect of consumer-based brand authenticity on customer satisfaction and brand loyalty - Uysal, Adem; Okumuş, Abdullah (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this study was to determine the effect of consumer-based brand authenticity (CBBA) on customer satisfaction (CS) and brand loyalty (BL). The moderating effect of the variable alternative attractiveness in the relationship between CS and BL was further investigated. The study compared and analyzed the difference between global sportswear brands and domestic ones and the difference between global chocolate brands and domestic ones in terms of CBBA, CS, BL and attractiveness of alternatives (AA). Design/methodology/approach Structural equation modeling and multigroup analysis were conducted in order to analyze the data collected from 600 consumers via face-to-face survey. Findings The results showed that quality commitment and heritage-sincerity, which are subdimensions of CBBA, had a significant positive effect on CS. Additionally, both of them affected CS differently in the comparison of the global brands with the domestic ones. Furthermore, CS had a significant positive effect on BL, and AA had a negative effect on BL. Originality/value This study deepens the insights into the effects of antecedents of CBBA on CS and BL, enhancing the research with quantitative analysis through two different product groups. The study provides important cues on which antecedents of CBBA help to strengthen the authenticity of brands of Turkish and global origin, and also differs in that it examines to what extent the effect of CBBA on CS and BL varies across global and domestic brands.
Keywords: Consumer-based brand authenticity; Customer satisfaction; Alternative attractiveness; Brand loyalty; Switching Barriers; Alternative Attractiveness; Conceptualization; Perceptions; Experience; Costs; Model